Delinking 'the two rupees': The devaluation dilemma and economic divergence in the decolonized subcontinent, September 1949–February 1951. (May 2023) - Ankit, Rakesh
Abstract: By looking at the September 1949 devaluation dilemma faced by the governments of Pakistan and India, this article argues that it was an early episode of divergence between them following partition. The reasons why Pakistan did not devalue when India did so have remained largely obscured in the historiography. Deeply contested, the decision was a determining event through which the state staked its claim for economic sovereignty, internally and externally. It led to a 17-month-long official trade deadlock, especially in the eastern region of partitioned Bengal. It ended when the two governments established an exchange ratio for the two rupees, no longer at par with each other. This interactive delinking of currencies was symptomatic of the improvisational decoupling of the colonial subcontinent's post-colonial states. In tracing its trajectory, this article contributes to the inconsiderable literature on why devaluation did not happen in Pakistan, revises the rationale offered, and presents the event as a contingent exercise in economic decolonization, generative of a post-colonial sovereign difference.